1996
DOI: 10.1007/s004110050016
|View full text |Cite
|
Sign up to set email alerts
|

Use of the true absorption coefficient as a measure of bioavailability of radiocaesium in ruminants

Abstract: Limitations of existing methods to describe the bioavailability of dietary radionuclides to ruminants (the transfer coefficient and apparent absorption coefficient) have led to the alternative suggestion of using the true absorption coefficient (A(t)). Various approaches to estimating A(t) for radiocaesium, involving the intravenous administration of a second isotope, are presented and discussed with reference to results from studies in which a range of radiocaesium sources were examined in sheep. Although est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The review by Howard [10] summarised reported mean F f values for ewes ingesting herbage contaminated by root uptake to be 0.3 -0.35 day · kg -1 . The availability of radiocaesium incorporated into herbage by root uptake has been shown to be similar to that of ionic radiocaesium in a number of studies [9,11]. However, there was a threefold range in F f values determined for individual sheep in the current study (0.19 -0.56 day · kg -1 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The review by Howard [10] summarised reported mean F f values for ewes ingesting herbage contaminated by root uptake to be 0.3 -0.35 day · kg -1 . The availability of radiocaesium incorporated into herbage by root uptake has been shown to be similar to that of ionic radiocaesium in a number of studies [9,11]. However, there was a threefold range in F f values determined for individual sheep in the current study (0.19 -0.56 day · kg -1 ).…”
Section: Discussionmentioning
confidence: 60%
“…Gastrointestinal absorption was determined as the true absorption coefficient (A t ) [9], where: (2) where EF, the endogenous faecal output of 137 Cs is given by: [16] b Where A t is the true absorption coefficient [9]; comparisons involving A t are for 12 animals (all other comparisons n = 22)…”
Section: Gastrointestinal Absorption Coefficient Of Radiocaesiummentioning
confidence: 99%
“…30% difference in the estimated values of 137 Cs intake and subsequent transfer coefficient to muscle. However, the mean of the seven A a values for contaminated herbage and ionic radiocaesium (CsCl) reported for sheep in the review of Mayes et al [21] is also 0.6, supporting the value selected here as the 'best estimate'.…”
Section: Estimation Of Radiocaesium Intakementioning
confidence: 68%
“…Whilst we consider that this is the most appropriate estimate of A a available for the conditions of the current study, reported values of A a range from 0.45 (grass hay fed as minor component of the diet) to 0.73 (CsCl) [21]. A choice of A a at the extremes of the reported range would result in ca.…”
Section: Estimation Of Radiocaesium Intakementioning
confidence: 94%
See 1 more Smart Citation